Access by the poor in Latin America's utility reform: Subsidies and service obligations - Omar O. Chisari; Antonio Estache; Catherine Waddams Price (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Any infrastructure reformers concerned with social issues in a developing country need to address two problems. The first is increasing access by the poor, and the second is ensuring consumption affordability, i.e. the ability of the poor to pay for both consumption and the amortization of the access charges. The two are related. The main concern of both policy makers and academics has been to identify options to cut costs so that coverage can be accelerated, focusing on cheaper technologies or on various financing/lending schemes. Latin America has been a pioneer in many aspects of such reform. Nevertheless, the Latin American experience shows that the poor are often the last to benefit from increased access due to reform. While in most countries, the rural poor tend to be omitted from reforms altogether, treatment of urban users varies considerably. Residential users have often been more exposed to increasing connection costs resulting from reform than commercial users, particularly where this element had previously been subsidized; therefore a more careful consideration of the key policy instruments to increase access by the poor may have strong social payoffs. This has led to various subsidy schemes of which Universal Service Obligation and Obligatory Service discussed in this study are `standard' tools used to increase access. The main focus of this study is to use both theory and practice to see how subsidies and service obligations can be designed, imposed and financed to increase coverage for a specific service (e.g. access to safe water, to electricity or to at least a public phone) as much and as fast as possible. The poor are particularly vulnerable to deterioration in macro-economic conditions. Design of access charges and penalties for arrears and delinquency need to take account of potential shocks. Argentina's experience shows that it is important not only to design the infrastructure appropriately, but also to maximize ongoing voluntary connection to services, particularly when the product is considered to be a `merit good'. – regulation ; service obligations ; Latin America
Keywords: K2; L5; L9; O2; 330; Versorgungswirtschaft; Regulierung; Lateinamerika; Soziale Folgen